Islamic Microfinance for Poverty Alleviation - Khatimah, Husnul; Isfandayani (SMART Insight, 2023)
Poverty is a serious problem faced by Indonesia. Most Indonesians are vulnerable to poverty. Various poverty alleviation programs have been attempted and initiated, both by the government and organizations outside the government. The process of changing poverty alleviation policies continues to be renewed. Because all parties realize that poverty is more caused by structural problems, the term structural poverty has emerged. Basically, the government has conducted many programs to alleviate poverty. But in reality, these programs have not been right on target. There is a need for a new design, so that it can be ensured that the program is right on direction and right on target. The Islamic economic system, including Islamic financial institutions, has the right and obligation to participate in managing the resources in this country. This study aims to determine the development of Islamic microfinance for poverty alleviation research trends published by leading journals on Islamic financial economics. The data analyzed consisted of 87 indexed research publications. The data is then processed and analyzed using the VoSviewer application to determine the bibliometric map of Islamic microfinance for poverty alleviation research development.